2015
DOI: 10.1155/2015/719497
|View full text |Cite
|
Sign up to set email alerts
|

Auditing of Monitoring and Respiratory Support Equipment in a Level III-C Neonatal Intensive Care Unit

Abstract: Background. Random safety audits (RSAs) are a safety tool but have not been widely used in hospitals. Objectives. To determine the frequency of proper use of equipment safety mechanisms in relation to monitoring and mechanical ventilation by performing RSAs. The study also determined whether factors related to the patient, time period, or characteristics of the area of admission influenced how the device safety systems were used. Methods. A prospective observational study was conducted in a level III-C Neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 25 publications
0
7
1
Order By: Relevance
“…Interestingly, our study showed similar global percentages of RRTSAs without defects as those reported by Bergon–Sendin et al who also conducted RRTSAs in different Spanish hospital neonatal areas and NICU work procedures and showed surprisingly low percentages of satisfactory audits. These authors detected defects in areas as important as the use of ventilation materials and respiratory monitoring (383 audits; adequate overall use: 33.7%), 13 resuscitation materials (296 audits; adequate overall use: 62.5%), 14 or infusion pumps (160 audits; adequate global use: 73.1%). 15 This low percentage of audits without defect should lead us to reflect upon whether our current hospital delivery room protocols are able to ensure the correct and complete preparation of positions used during the care of newborns at the time of their delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, our study showed similar global percentages of RRTSAs without defects as those reported by Bergon–Sendin et al who also conducted RRTSAs in different Spanish hospital neonatal areas and NICU work procedures and showed surprisingly low percentages of satisfactory audits. These authors detected defects in areas as important as the use of ventilation materials and respiratory monitoring (383 audits; adequate overall use: 33.7%), 13 resuscitation materials (296 audits; adequate overall use: 62.5%), 14 or infusion pumps (160 audits; adequate global use: 73.1%). 15 This low percentage of audits without defect should lead us to reflect upon whether our current hospital delivery room protocols are able to ensure the correct and complete preparation of positions used during the care of newborns at the time of their delivery.…”
Section: Discussionmentioning
confidence: 99%
“…7,12 Several studies on RRTSAs have been performed in neonatal intensive care units (NICUs) for various procedures and materials (for example, ventilation and respiratory monitoring, materials available for resuscitation, infusion pumps, and prevention of nosocomial infections). 11,[13][14][15][16] However, to the best of our knowledge, no specific work on RRTSAs has been performed for neonatal delivery room CPR stabilization areas. Thus, the objective of this study was to use audits to verify the level of preparation of these areas, analyze any circumstances that could influence their correct availability, and check the value of this quality-control tool to prevent safety-related incidents in this field.…”
mentioning
confidence: 99%
“…Although most alarms recorded lasted Ͻ 1 min, the study noted that some infants were subjected to audible alarms for 10% of the day, which may negatively affect recovery and neurodevelopment. 30,31 In addition, this contributes to feelings of fear and anxiety in patients and visitors. 27…”
Section: Negative Impact Of Noisementioning
confidence: 99%
“…When performing such audits in a NICU setting, the rate of appropriate overall use of monitoring and respiratory support equipment was only 34%, that is, these devices were inappropriately used for two-thirds of the time. Rates of appropriate use were lowest for pulse oximeter saturation (SpO 2 ) target and respiratory rate alarms on patient monitors, and for minute volume alarms on ventilators 4. Thus, as now in part also shown by Belteki and Morley for ventilators, both ventilators and pulse oximeters are the devices we should focus on first if we want to tackle alarm rates in the NICU.…”
mentioning
confidence: 93%